Comparative analysis of microRNA and mRNA expression profiles in cells and exosomes under toluene exposure - Lim, Jung-hee; Song, Mi-Kyung; Cho, Yoon; Kim, Woong; Han, Sung Ok; Ryu, Jae-Chun (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Recent studies have illustrated the growing importance of exosomes (small extracellular vesicles) and their constituent microRNAs (miRNAs) in the fields of toxicology and pathology. The mechanism of toxicity of toluene, a highly-prevalent and volatile organic compound, is largely unknown. To examine the role of miRNAs in toluene induced toxicity, we investigated miRNAs and toluene-induced gene expression in HL-60 human promyelocytic leukemia cells and exosomes using microarrays. A total of 54 miRNAs were differentially expressed in HL-60 cell lines exposed to toluene and exosomes from the cells. Four out of the 54 miRNAs (hsa-miR-1290, hsa-miR-718, hsa-miR-3663-3p, and hsa-miR-320c) were subsequently validated by qRT-PCR. Integrated analysis of miRNA and mRNA expression profiles identified 8 miRNA-mRNA correlations. By performing Comparative Toxicogenomics Database analysis, we found that the eight putative target genes of the differentially expressed miRNAs under toluene exposure (EXOSC6, RHOH, GFER, HERC2, GOLGA4, SLC7A11, GCLM, and BACH1) are related to diverse disease categories such as nervous system disease, cancer, cardiovascular disease, and respiratory tract disease. In conclusion, our data demonstrated that miRNA-mRNA networks provide a better understanding of toxicological mechanism caused by environmental pollutants in vitro using HL-60 cells and exosomes. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: CENTRAL-NERVOUS-SYSTEM; INDOOR AIR-POLLUTION; OXIDATIVE STRESS; CANCER; MIRNA; HEALTH; BACH1; ACTIVATION; BIOMARKERS; MECHANISM